An evaluation of the case for a congestion tax in Australia - Pearce, Prafula; Pinto, Dale (Taxation Institue of Australia, 2015)
Traffic congestion has become a growing concern in most cities in Australia. A 2014 report by the Economic Regulation Authority (ERA) highlighted the need to implement a congestion charge in Perth. This article examines factors that cause congestion and alternative ways of dealing with congestion in Australia. Specifically, the article examines whether introducing a congestion tax could provide an effective means of resolving traffic congestion in Australian cities. Studies and results from other jurisdictions are examined in order to help inform the policies that Australia should adopt. It is submitted that an inquiry into congestion charges should include a wider investigation, including motor vehicle tax reform, city planning, redirection of revenues and a longer strategic plan. The article also recognises that congestion charging, if implemented, may have other implications for which Australian cities may not be ready.